The Effect of Spoilers on the Enjoyment of Short Stories. Issue 7 (2nd October 2016) - Levine, William H.; Betzner, Michelle; Autry, Kevin S.
Abstract : Recent research has provided evidence that the information provided before a story—a spoiler—may increase the enjoyment of that story, perhaps by increasing the processing fluency experienced during reading. In one experiment, we tested the reliability of these findings by closely replicating existing methods and the generality of these findings by using different stories. We also examined the role of processing fluency in the effect of spoilers by measuring reading time. Finally, we examined the influence of spoilers presented mid-story, after a reader has had a chance to get invested in the story. We found that spoilers presented before a story reduced enjoyment, whereas those presented mid-story had no discernable effect. The difference between our findings and those in the literature are discussed with respect to types of spoilers as well as potentially critical methodological factors.